2016
DOI: 10.1016/j.neuron.2016.01.033
|View full text |Cite
|
Sign up to set email alerts
|

Context-Dependent Gait Choice Elicited by EphA4 Mutation in Lbx1 Spinal Interneurons

Abstract: The most commonly used locomotor strategy in rodents is left-right limb alternation. Mutation of the axon guidance molecule EphA4 profoundly alters this basic locomotor pattern to synchrony. Here we report that conditional mutation of EphA4 in spinal interneurons expressing the transcription factor Lbx1 degrades the robustness in the expression of left-right alternating gait during development. Lbx1 EphA4 conditional mice exhibit alternating gait when walking on ground, but synchronous gait in environments wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…In dorsal spinal cord, the spatial organization of Lbx1-derived premotor interneurons determines their role, i.e., flexor interneurons born at e10.5 migrate laterally in lamina VI while extensor interneurons born at e12.5 remain closer to the central canal (Tripodi et al, 2011). EphA4 in these cells determines their localization as well as their axonal projections and their contribution to left-right motor alternation (Satoh et al, 2016). Likewise, the sensory cues that trigger motor responses are linked to the ML position of dorsal premotor interneurons in the deep dorsal horn (Hilde et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In dorsal spinal cord, the spatial organization of Lbx1-derived premotor interneurons determines their role, i.e., flexor interneurons born at e10.5 migrate laterally in lamina VI while extensor interneurons born at e12.5 remain closer to the central canal (Tripodi et al, 2011). EphA4 in these cells determines their localization as well as their axonal projections and their contribution to left-right motor alternation (Satoh et al, 2016). Likewise, the sensory cues that trigger motor responses are linked to the ML position of dorsal premotor interneurons in the deep dorsal horn (Hilde et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identification of the molecular regulators of neuronal migration and distribution in the spinal cord is important to understand circuit formation and neural activity. Interestingly, the interneuron populations altered in absence of OC factors are involved in motor control, either modulating motor neurons (Andersson et al, 2012; Bui et al, 2013; Goetz et al, 2015; Satoh et al, 2016) or ventral premotor interneuron activity (Levine et al, 2014; Hilde et al, 2016) or mediating presynaptic inhibitory control of proprioceptive sensory neurons (Betley et al, 2009; Fink et al, 2014). Hence, OC factors could have been recruited in different neuronal subsets to coordinate the development of distinct populations eventually involved in motor circuits.…”
Section: Discussionmentioning
confidence: 99%
“…G-deleted, rabies-mCherry or rabies-eGFP (rabies-FP) coated with G protein or EnvA-coated variants were amplified and purified from local stocks following established protocols (Osakada & Callaway, 2013;Stepien, Tripodi, & Arber, 2010;Wickersham et al, 2007). The following AAVs used in this study were previously described (Basaldella, Takeoka, Sigrist, & Arber, 2015;Esposito et al, 2014;Pivetta, Esposito, Sigrist, & Arber, 2014;Satoh, Pudenz, & Arber, 2016;Takeoka, Vollenweider, Courtine, & Arber, 2014) (Fenno et al, 2014), and AAV-flex-FLP-H2B-V5 was designed in analogy to above constructs with an FLP sequence successfully used before (Pivetta et al, 2014). For non-conditional expression of tagged markers to assess injection specificity, we used AAV-H2B-10XMyc or AAV-TdTomato (AAV-marker).…”
Section: Virus Production and Injectionsmentioning
confidence: 99%
“…In more recent work, we demonstrated that interneurons premotor to motor neurons regulating postural muscles involved in trunk stability, and with very distinct function from limb muscles, show a bilaterally symmetrical distribution in the spinal cord, while counterparts associated with the control of limb muscles are biased toward the ipsilateral spinal cord (Goetz et al , ). We also found that alternation of axon guidance molecules on genetically defined interneurons downstream of transcription factors can alter premotor connectivity patterns and lead to behavioral abnormalities (Satoh et al , ). Lastly, the majority of studies on spinal interneurons in the past and in particular the ones linking developmental transcriptional identity to locomotor function focused mostly on local interneuron circuitry (Arber, ).…”
Section: The Spinal Cord As a Highly Organized Final Executive Centermentioning
confidence: 83%